Epidemiological dynamics and rising trends of MRSA in Saudi Arabia: a 12-year observational study - Subramanian, Anandhalakshmi; Shabi, Yahya; Alazraqi, Tarik; Abdelrahim, Ihab M.; Hamid, Mohamed E.; Al Bshabshe, Ali; Algarni, Abdullah; Habbash, Sara; Mohammed, Safia Abdullah; Alqahtani, Abdulah Jarboa; Elsherif, Rasha; Bawazeer, Abdulah O. S.; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) presents serious clinical and public health complications, and Staphylococcus aureus is still a major cause of morbidity and mortality globally. The objective of this study was to assess the temporal dynamics, microbiological traits, and epidemiological trends of methicillin-susceptible S. aureus (MSSA) and MRSA isolates over a twelve-year period in a tertiary care facility.MethodsThis retrospective cohort study analyzed the data of all confirmed S. aureus isolates collected between January 2013 and June 2024. Identification and antimicrobial susceptibility testing were performed using automated methods according to CLSI guidelines. MRSA was confirmed by detection of the mecA gene in all isolates using the GeneXpert MRSA assay. Additionally, 100 randomly selected MRSA isolates were further tested with the same platform for the presence of the SCCmec gene; all of which were positive. Demographic, clinical, and microbiological data were evaluated, and Generalized Linear Models were applied to assess temporal trends in oxacillin resistance.ResultsThe total of confirmed S. aureus isolates was 4,267. MRSA accounted for 52.7% (2,250) of all S. aureus isolates. It was significantly more prevalent in patients with COVID-19 (62.5%), diabetes mellitus (56.4%), and end-stage renal disease (52.7%) (p = 0.041). MRSA rates were higher in inpatient settings, particularly in surgical (56.0%), ICU/IMCU (53.4%), and medical wards (52.7%) (p < 0.001). While culture sources did not differ significantly between MRSA and MSSA (p = 0.212), MRSA was more commonly found in blood, skin, and abscess samples. Over time, MRSA prevalence increased across all wards, with the surgical ward showing the most significant rise (OR = 1.115; 95% CI: 1.080–1.152; p < 0.001).ConclusionThis study demonstrates a rising burden of MRSA over the past decade, especially among vulnerable populations. The findings underscore the need for strengthened infection control, targeted antimicrobial stewardship, and ongoing surveillance to combat MRSA in Saudi Arabia and similar high-risk settings.